Forests adrift : currents shaping the future of northeastern trees - Canham, Charles Draper William, 1954- (Future series (Yale University Press), 2020)
A captivating analysis of the past, present, and future of northeastern forests and the forces that have shaped them. The northeastern United States is one of the most densely forested regions in the country, yet its history of growth, destruction, and renewal are for the most part poorly understood-even by specialists. In this engaging look at both the impermanence and the resilience of the northeastern forest ecosystems, Charles D. Canham provides a synthesis of modern ecological research and explores critical threats that include logging, fire suppression, disease, air pollution, invasive species, and climate change. Providing a historical perspective on how northeastern forests have changed since the arrival of European settlers, Canham also utilizes new theoretical models to predict how these ecosystems will change and adapt to an uncertain future. This is an informed and accessible investigation of an endangered natural landscape that examines the ramifications of the scientific controversies and ethical dilemmas shaping the future of northeastern forests.--